Pemberdayaan Pelaku Seni Jaranan Nganjuk Dalam Menangani Cidera Melalui Keterampilan Masase Terapi - Sifa, Agus; Hariyato, Agus; Suryandoko, Welly (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
Community Service entitled Empowering Jaranan Nganjuk Performers in Handling Injuries Through Massage Therapy Skills has a fundamental goal of implementing it in society, namely welfare by always maintaining health by maintaining physical condition. Jaranan actors need to be empowered so that their standard of living and vitality are better. So, through this service, you can make a good contribution, because the main purpose of carrying out this service is so that the actors can be independent in dealing with minor injuries or serious injuries during or after the show. Empowerment is carried out in the form of 1) Involvement of partners as training participants in massage therapy for injuries, 2) Involvement in handling injuries through massage therapy skills, 3) Involving other Jaranan actors to be empowered to have massage therapy skills, 5) Involvement in forming therapeutic massage groups to Jaranan perpetrators. The main goal is for practitioners of the Jaranan Art to understand the benefits, techniques, and practices of this therapeutic massage. Next is to provide legitimacy for Jaranan performers who are proficient at performing therapeutic massage in the form of certification that each Jaranan performer has the skills to handle Jaranan performers when they are injured.